Stochastic informative expert system for investment - Rutkauskas, Aleksandras Vytautas; Stasytytė, Viktorija (Journal of Business Economics and Management, 2020)
The stochastic nature of investment process implies that it should be treated not unambiguously. Instead of concentrating only on possible return, it is worth analysing three parameters when we discuss the future investment results. These parameters are return possibility, reliability of this possibility, and the riskiness. The stochastic informative expert system for investment allows to analyse the behaviour of financial markets, forecasting the dynamics of stock prices and, along with that, rationally allocating investment resources. The proposed system is based on the adequate portfolio model, previously developed by the authors. Considering the real-time characteristics of financial markets, the system can be useful for individual investors, as well as for institutional investors, such as investment funds. Also, the authors propose the original risk tolerance determination methodology, which divides investors into three categories according their risk tolerance. The system can be applicable not only to capital markets, but also to other business or macroeconomic processes. As an example, a portfolio of the interaction of macroeconomic indicators with USA, UK, and Lithuanian data is developed. Such results could be useful for economists and governments in order to attain the higher value added in a particular country.